VOKATIF PENGHORMATAN ADÉN DAN DÉN ‘TUAN’ BAHASA SUNDA DALAM PERSPEKTIF SINTAKSIS - Wahya (Jurnal Kajian Budaya dan Humaniora, 2025)
This study is a study of the Sundanese honorific vocatives Dén and Adén ‘Sir’ from a syntactic perspective. This vocative is used to respectfully address a certain person because they are socially in a certain social class. There are quite a lot of honorific vocatives in Sundanese, including the vocative Adén ‘Tuan’ and the vocative Dén ‘Tuan’ which are morphologically a form of a fragment of Radén. This vocative is addressed to male speech partners. This study is descriptive qualitative. Data provision uses the listening method with note-taking techniques. Data analysis uses a syntactic approach. The data source used is a single written data source, namely a Sundanese novel entitled Kembang Rumah Tangga by Tjaraka (1996). The reason for using this data source is because it contains a lot of data that is needed and as a sample. Based on the data sources used, 35 sentences were found containing honorific vocatives, namely the single vocatives Adén and Dén and the combination of honorific and proper name vocatives, namely Dén Sujana. The honorific vocatives Adén and Dén totaled 34 data with details of the Adén vocative totaling 5 data, while the Dén vocative totaling 29 data. In addition, the honorific vocative Dén was also found combined with the proper name vocative Sujana which formed the combination vocative Dén Sujana which totaled only 1 data. Thus, based on its form, this honorific vocative is dominated by the single vocative Dén. Based on the types of sentences containing the honorific vocatives above, there were 5 declarative sentences, 1 imperative sentence, 10 interrogative sentences, and 19 exclamative sentences. Thus, the types of sentences containing the honorific vocatives are dominated by exclamative sentences. The Adén vocative is found in interrogative and exclamative sentences. The Dén vocative is found in declarative, imperative, interrogative and exclamative sentences. The Dén Sujana vocative is only found in exclamative sentences. Based on the distribution in the sentence, the honorific vocatives above are found at the beginning of the sentence or initial totaling 2 data, in the middle of the sentence or medial totaling 12 data, and at the end of the sentence or final totaling 21 data. Thus, this honorific vocative is dominated by the final position of the sentence.